Spatially explicit action research for coastal fisheries management. - Tara N Lawrence; R S Bhalla (PLoS ONE)
We worked with artisanal fisherfolk along the Coromandel coast in two districts of Tamil Nadu and the Union Territory of Pondicherry in South India to map and quantify catch, gear and crew details for all fishing craft along 120 km. Spatially explicit fisheries data were collected to understand the distribution of fishing effort and to identify high pressure fishing zones. Approximately 7,945 square kilometres of fishing grounds were surveyed and 3,427 fishing trips were observed using nine GPS enabled echo-sounders operated by fishermen. Data were visualised and non parametric statistical analysis revealed distinct patterns in fishing effort, high density fishing zones and large overlaps in zones between traditional, motorised and mechanised craft. Existing marine fishing regulations for the respective regions were also evaluated and violations were mapped. Results were presented in each of the villages and then in district wide meetings with community leaders to spur discussions on resource based conflicts and fisheries management. Our findings suggest that the present trajectory of resource over-exploitation, the use of destructive fishing methods combined with the lack of compliance to current regulations will lead to a collapse of the small scale fishing industry and further intensify conflicts within the community. Recommendations made by fishing community leaders are presented and their role in local fisheries management is discussed. This study is the first of its kind for this region and can easily be replicated at regional scales to develop a better understanding of the spatial extent and nature of small scale fisheries, including conflict, for the purpose of fisheries management.